A relational psychoanalytic exploration of the intergenerational transmission of trauma from mothers to their adult children - Bradfield, Bruce Christopher (Department of Psychology, 2014)
This dissertation aims to investigate and describe the inter-generational transmission of trauma from mothers with a history of interpersonal trauma to their adult children, in the context of the relationship between mother and child. Through this the research aims to articulate the conscious and unconscious relational and intra-psychic processes by which trauma is transmitted from mothers to their adult children.